Water-Soluble and Cleavable Quercetin-Amino Acid Conjugates as Safe Modulators for P-Glycoprotein-Based Multidrug Resistance - Kim, Mi Kyoung; Choo, Hyunah; Chong, Youhoon (AMER CHEMICAL SOC, 2014)
Quercetinamino acid conjugates with alanine or glutamic acid moiety attached at 7-O and/or 3-O position of quercetin were prepared, and their multidrug resistance (MDR)-modulatory effects were evaluated. A quercetinglutamic acid conjugate, 7-O-Glu-Q (3a), was as potent as verapamil in reversing MDR and sensitized MDR MES-SA/Dx5 cells to various anticancer drugs with EC50 values of 0.80.9 mu M. Analysis on Rh-123 accumulation confirmed that 3a inhibits drug efflux by Pgp, and Pgp ATPase assay showed that 3a interacts with the drug-binding site of Pgp to stimulate its ATPase activity. Physicochemical analysis of 3a revealed that solubility, stability, and cellular uptake of quercetin were significantly improved by the glutamic acid promoiety, which eventually dissociates from 3a to produce quercetin and quercetin metabolites in intracellular milieu. Taken together, potent MDR-modulating activity along with intracellular conversion into the natural flavonoid quercetin warrants development of the quercetinamino acid conjugates as safe MDR modulators.
Keywords: CANCER CELL-LINE; IN-VITRO; FLAVONOID DIMERS; APIGENIN HOMODIMERS; BIVALENT MODULATORS; PROTEIN-KINASES; HYDROXYL-GROUPS; FLOW-CYTOMETRY; CYCLOSPORINE-A; REVERSAL